2022
DOI: 10.1002/marc.202100873
|View full text |Cite
|
Sign up to set email alerts
|

Flame‐Retardant PEDOT:PSS/LDHs/Leather Flexible Strain Sensor for Human Motion Detection

Abstract: Flexible piezoresistive sensors have demonstrated great potential in human–motion–detection applications. However, it still remains a challenge to fabricate strain sensors with high sensitivity, broad sensing range, and good linear response to strain. In this report, a simple and scalable fabrication strategy is developed to construct high performance strain sensors by using leather as the substrates to filtrate poly(3,4‐ethylenedioxythiophene): poly(4‐styrenesulfonate) (PEDOT:PSS) modified layered double hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…In addition, electrical stability of the CNT/MXene/CNT/TPU strain sensor is further characterized by the I – V curve under different stretching (Figure S6) and the Δ R / R 0 -strain curve at different stretching rates (Figure S7), which enable the sensor to accurately and timely transmit the signals captured in human motion detection to back-end processing equipment. Additionally, the performances of the CNT/MXene/CNT/TPU strain sensor and recent crack-based strain sensors are compared in terms of sensing range and sensitivity (Figure h), ,, and the detailed parameters are shown in Table S1. It can be found that crack-based strain sensors are generally unable to combine a wide sensing range and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, electrical stability of the CNT/MXene/CNT/TPU strain sensor is further characterized by the I – V curve under different stretching (Figure S6) and the Δ R / R 0 -strain curve at different stretching rates (Figure S7), which enable the sensor to accurately and timely transmit the signals captured in human motion detection to back-end processing equipment. Additionally, the performances of the CNT/MXene/CNT/TPU strain sensor and recent crack-based strain sensors are compared in terms of sensing range and sensitivity (Figure h), ,, and the detailed parameters are shown in Table S1. It can be found that crack-based strain sensors are generally unable to combine a wide sensing range and high sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…24 Fabricated leather consists of collagen fiber bundles and still inherits the nanomicro structure from an animal skin. 25 The special hierarchical structure endows leather with biocompatibility and softness similar to those of human skin as well as excellent durability and breathability, making it suitable for long-time contact with human skin without irritation and discomfort. 26 Thus, leather has the potential to become an ideal flexible substrate for wearable electronics.…”
Section: Introductionmentioning
confidence: 99%
“…The results from the limiting oxygen index test, vertical burning test, and microscale combustion calorimetric analysis indicated that the obtained sensor possessed desirable flame retarding properties. 4 PA also endowed good flame retardancy for conductive polymer-based sensors, for example a polyaniline sensor is capable of selfextinguishing in 20 s after ignition by doping with PA. 5 Apart from PA, two-dimensional nanomaterials, such as MXene 6 and layered double hydroxides, 7 could provide self-extinguishment ability or shortened burning time when heated by the flame for a short time. Despite this, the current reports mainly examine the flame-retardant properties of the CPC-based sensors separately from the sensing ability, while the smooth operation just in the fire seems to be more valuable in the practical application for the sensors.…”
Section: Introductionmentioning
confidence: 99%